Обобщенная модель системного синтеза автоматической трансмиссии - Нефёдов, Л. И.; Осьмачко, А. А. (Eastern-European Journal of Enterprise Technologies, 2020)
The general model of a choice and assess automatic transmission, and also its decomposition on separate tasks of structural and parametrical synthesis